Descriptive and Normative Norms in Film Adaptation: The Hays Office and the American Film Noir - Cattrysse, Patrick (Cinémas)

(untitled) (Cinémas, 1996)
The study of the normative and descriptive rules of adaptation in the American film noir replaces the usual textual analysis with an intersystemic analysis of the process of adaptation. Avoiding in this way an evaluation of the accuracy of the film with respect to the novel makes it possible to examine how certain social norms and certain narrative models will determine the passage from the written text to the screen.